Zasady postępowania w urazach sportowców wyczynowych - Kraszewski, K.; Крашевський, K. (Східноєвропейський національний університет ім.Лесі Українки, 2012)
Sports injuries occur most often in team sports, especially football, skiing, martial arts, motor sports. The most common types of injuries are fractures, sprains, damaged ligaments cross the knee and elbow ligaments. Handling injuries are divided into three stages: action immediately after the injury, treatment and rehabilitation. Treatment according to the injury may be operational or conservative. Arthroscopy is very important treatment’s method. In rehabilitation, there are three periods: immediately after treatment, appropriate rehabilitation period and the period of transition between rehabilitation and training, taking correctly. The problems faced by the sports physician are the pressures of rapid return to sport player and selection of the most fashionable treatments. Only the right action after injury may allow the player to return to full form. Спортивні травми найчастіше трапляються в командних іграх (регбі, футбол, гандбол), боксі, боротьбі, мотоциклетних гонках та ін. Найбільш частими травмами в спортсменів є переломи ніг і рук, вивихи, травми колін та ліктів. Період лікування травмованих спортсменів можна поділити на три етапи – надання медичної допомоги відразу після травми, безпосередне лікування, реабілітація. Проблеми травмування, із якими має справу лікар, пов’язані зі швидким поверненням травмованих спортсменів до регулярних тренувальних занять і виступів у змаганнях. Ключові слова: спортсмени, травми, лікування, реабілітація.
Засади діяльності в ситуації травматизму в спортсменів
Keywords: sports injury; treatment sports injuries; rehabilitation of athletes; спортсмени; травми; лікування; реабілітація